EVALUASI PENERAPAN SISTEM PENGENDALIAN INTERN PERSEDIAAN BARANG DAGANGAN PADA BLIBLI.COM CABANG KARAWACI - Maireni Maireni; Pandoyo Pandoyo (JAMBIS : Jurnal Administrasi Bisnis, 2021)
Supply is one of the important asset had by company. Because supply represent asset of hence must be done internal control which is good to taking care of the supply from ugly things is which is possible happened the. System of internal control of stock to control and manage the stock. Especial target from operation to the supply is protect the supply and report it precisely in financial statement. Method used by is approach method qualitative that is, descriptive analysis. From research result at Blibli.Com Cabang Karawaci represent a peripatetic company is area of E- Commerce, or more knowledgeable as retail. System evaluation, internal control to the supply have effective, where existence of duty dissociation of between functions of related to revenue and expenditure goods. Monitoring to merchanidise stock is also conducted routinely each;every one month once by warehouse shares through the stock activity hospitalize them. System of inventory control of merchandise at Blibli.Com Cabang Karawaci have walked better.